2020
DOI: 10.1016/j.crwh.2019.e00165
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic hysterectomy to manage uterine rupture due to placenta percreta in the first trimester: A case report

Abstract: Placenta percreta causing uterine rupture is a rare complication of pregnancy. It is most commonly diagnosed after the second trimester and can lead to significant morbidity necessitating abdominal hysterectomy of a gravid or immediately postpartum uterus. We describe a patient who presented with abdominal pain at 13 weeks of gestation and was diagnosed with placenta percreta during laparoscopy for presumed appendicitis. Intraoperatively, placenta was seen perforating the uterine fundus and 1 l of hemoperitone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The remaining 28 cases included intraoperative images in 10 cases, 25,35,40,45,48,52,55,59,61,63 immediate postoperative images of hysterectomy specimens in 2 cases, 33,57 laboratory gross images in 10 cases, 28,30,36,39,42,43,46,47,50,56 and combined intraoperative and postoperative images in 6 cases. 37,49,51,54,58,62 The most common macroscopic description (13 of 28 cases [46.4%]) was that of uterine rupture with bulging of the Distribution for the placenta accreta spectrum grading based on the intraoperative findings in the 101 cases of the cohort using the International Federation of Gynecology and Obstetrics' classification 1 Original Research OBSTETRICS ajog.org placenta or both placenta and fetus. Ruptures were reported as fundal in 3 cases 25,33,37 and cervical in 1 case.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 28 cases included intraoperative images in 10 cases, 25,35,40,45,48,52,55,59,61,63 immediate postoperative images of hysterectomy specimens in 2 cases, 33,57 laboratory gross images in 10 cases, 28,30,36,39,42,43,46,47,50,56 and combined intraoperative and postoperative images in 6 cases. 37,49,51,54,58,62 The most common macroscopic description (13 of 28 cases [46.4%]) was that of uterine rupture with bulging of the Distribution for the placenta accreta spectrum grading based on the intraoperative findings in the 101 cases of the cohort using the International Federation of Gynecology and Obstetrics' classification 1 Original Research OBSTETRICS ajog.org placenta or both placenta and fetus. Ruptures were reported as fundal in 3 cases 25,33,37 and cervical in 1 case.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…The review of the published microscopic images found chorionic villi directly apposed to a morphologically normal myometrium in 13 cases, 26,35,37,41,43e48,50,51,55 to a scarred uterine myometrium in 9 cases, 24,29e32,49,52,54,60 and to both normal and scarred myometrial tissues in 4 cases. 38,42,58,62 In 2 cases, the villi were apposed on the cervical stroma, 27,29 and in 3 cases, the villi were bounded by fibrinoid. 38,44,58 In 1 case, EVTs might be present in the bowel fat tissue outside a scarred uterine wall after myomectomy.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Lee et al recently reported eleven published cases of uterine rupture between 13 and 21 weeks and suggested suspecting rupture if ultrasound shows intraperitoneal fluid with gravid uterus. 6 Our case had a documented intrauterine pregnancy with well-maintained uterine contour and in absence of any abdominal tenderness, deteriorating vitals, or signs of shock, any obstetrical emergency seemed unlikely. Besides coarse liver echotexture with ascites with deranged liver function tests suggested liver pathology.…”
Section: Discussionmentioning
confidence: 75%
“…10 Laparoscopic approach may be favoured in haemodynamically stable patients when avoiding uterine manipulator, intrauterine vasopressin, lateralizing ureters and retroperitoneal dissection to secure uterine arteries at the origin may increase safety margin. 6 In our case, hysterectomy was performed as tissues at the defect were very friable to hold any suture and patient had two live children.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation